PERHITUNGAN PROFIL TEGANGAN PADA SISTEM DISTRIBUSI MENGGUNAKAN MATRIX ADMITANSI DAN MATRIX IMPEDANSI BUS - Sukmawidjaja, Maula (Jurnal Teknik Elektro, 2008)
A very important problem in the design and operation of a distribution system is thecalculation of the voltage profile within specified limits at various points in the system. Inthis text we shall develop methods by which we can calculate the voltage, current, and powerat any point in a distribution line provided we know these values at one point, usually at oneend of the line. The continued development of large, high-speed digital computers havebrought about a change in the relative importance of various techniques in the solution oflarge distribution networks. One of particular importance is the introduction of busadmittance and bus impedance matrices method which will prove to be very useful in thecalculation of the voltage profile in the distribution networks.Keywords: voltage profile, bus admittance, bus impedance, matrices